Congenital platelet disorders and understanding of platelet function. (29th November 2013) - Nurden, Alan T.; Nurden, Paquita
Summary Genetic defects of platelets constitute rare diseases that include bleeding syndromes of autosomal dominant, recessive or X‐linked inheritance. They affect platelet production, resulting in a low circulating platelet count and changes in platelet morphology, platelet function, or a combination of both with altered megakaryopoiesis and a defective platelet response. As a result, blood platelets fail to fulfil their haemostatic function. Most studied of the platelet function disorders are deficiencies of glycoprotein mediators of adhesion and aggregation while defects of primary receptors for stimuli include the P2Y12 ADP receptor. Studies on inherited defects of (i) secretion from storage organelles (dense granules, α‐granules), (ii) the platelet cytoskeleton and (iii) the generation of pro‐coagulant activity have identified genes indirectly controlling the functional response. Signalling pathway defects leading to agonist‐specific modifications of platelet aggregation are the current target of exome‐sequencing strategies. We now review recent advances in the molecular characterization of platelet function defects.